Coalition building in a spatial economy - Joachim Henkel; Konrad O. Stahl; Uwe Walz (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1997)
We analyze the possibility and consequences of coalition-formation amongst suppliers of retail services. We first provide a framework in which producers of Substitutes have an incentive to Cluster in market places in order to attract consumers dispersed in space. Owing to spatial externalities, the resulting spatial equilibrium can be welfare suboptimal. We characterize regimes in which we find too little and those in which there is too much agglomeration of firms. We analyze the role of coalitions of firms (e.g. initiated by a land developer) in this framework and show that such coalitions can overcome the suboptimality of the decentralized spatial allocation.
Keywords: D40; L13; R12; 330; endogenous agglomerations; monopolistic competition; coalition building; Einzelhandelsstandort; Produktdifferenzierung; Standorttheorie; Agglomerationseffekt; Monopolistischer Wettbewerb; Koalition; Theorie